(untitled) (Modern education and development, 2025)
This article analyzes modern technologies in the field of gas supply. In particular, innovative solutions such as smart meters, GIS and SCADA systems, sensor control, as well as biogas and artificial methane production are considered. These technologies play an important role in increasing safety, reducing losses, and ensuring energy stability. The article is intended for use in the modernization of gas networks from a technical and practical point of view.